Metabolic consequences on platelet parameters: Mean platelet volume and platelet distribution width in type 2 diabetes mellitus - Nakhro, Nuneno; Khambra, Poonam; Sharma, Sonam; T. Banikanta Singha (Asian Journal of Medical Sciences, 2024)
Background: Diabetes mellitus encompasses metabolic disorders marked by chronic hyperglycemia, leading to various complications. It is considered a prothrombotic state associated with increased platelet reactivity. Parameters such as mean platelet volume (MPV) and platelet distribution width (PDW), which are indicative of platelet size, enzymatic activity, and prothrombotic risk, can be readily assessed during routine hematological analysis, facilitating early detection of this prothrombotic state. Aims and Objectives: The study aimed to investigate the varied alterations in platelet parameters in type 2 diabetes mellitus (T2DM) patients and tried to elucidate these parameters’ predictive role in diabetes complications. Materials and Methods: This prospective cross-sectional study was conducted between February 2022 and February 2024, involving 100 patients with T2DM and 100 healthy non-diabetic individuals. MPV, PDW, fasting blood glucose (FBS), and glycated hemoglobin (HbA1c) levels were measured and analyzed. Statistical analysis was carried out using the Student’s t-test, Mann–Whitney U-test, Chi-square test, and Spearman’s correlation tests in the Statistical Package for the Social Sciences software (version 21.0). Results: Most of the patients were in the age group of 40–70 years with male predominance. In comparing the 100 diabetics and 100 non-diabetics groups, MPV and PDW levels were notably higher in diabetics (11.46±1.75 vs. 9.40±1.02 fl, 21±2.57 vs. 16.72±1.48%) with statistical significance (P<0.01). Similarly, FBS and HbA1C levels were elevated among diabetics (179.38±70.25 vs. 90.64±5.93, 7.83±2.24 vs. 5.02±0.64) along with a positive correlation between platelet indices (MPV and PDW) and FBS, HbA1c levels in patients with T2DM. In addition, diabetic patients with complications exhibit significantly higher MPV, PDW, FBS, and HbA1c levels compared to those without complications. Conclusion: MPV and PDW levels show significant alterations in T2DM patients, with consistently elevated values, especially in those with complications. This underscores their potential importance as key indicators alongside glycemic indices such as FBS and HbA1c, in monitoring diabetes progression and anticipating associated complications.